2010
DOI: 10.1128/jvi.00024-10
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Autophagy during Lytic Replication by the Kaposi's Sarcoma-Associated Herpesvirus Replication and Transcription Activator

Abstract: Autophagy is one of two major degradation systems in eukaryotic cells. The degradation mechanism of autophagy is required to maintain the balance between the biosynthetic and catabolic processes and also contributes to defense against invading pathogens. Recent studies suggest that a number of viruses can evade or subvert the host cell autophagic pathway to enhance their own replication. Here, we investigated the effect of autophagy on the KSHV (Kaposi's sarcoma-associated herpesvirus) life cycle. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 68 publications
4
58
3
1
Order By: Relevance
“…It seems to be dependent on the virus, on the phases of its life cycle, and on host cell type. Regarding the relationship between autophagy and viral replication, it has been demonstrated that several viruses, such as HCV (42) and HBV, stimulate an incomplete autophagy (43) and that autophagy is involved in KSHV replication (15). However, a KSHV protein, K7, expressed during its lytic phase, is able to block the autophagic process (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems to be dependent on the virus, on the phases of its life cycle, and on host cell type. Regarding the relationship between autophagy and viral replication, it has been demonstrated that several viruses, such as HCV (42) and HBV, stimulate an incomplete autophagy (43) and that autophagy is involved in KSHV replication (15). However, a KSHV protein, K7, expressed during its lytic phase, is able to block the autophagic process (44).…”
Section: Discussionmentioning
confidence: 99%
“…The autophagic pathway can be induced or blocked at different steps by viruses, depending on the phase of their life cycle and on the host cell types. For example, autophagy is enhanced during Kaposi' sarcoma-associated herpesvirus (KSHV) replication (15), allowing the virus to benefit from the autophagic vesicles, termed autophagosomes, for its transportation into the cell cytoplasm. In particular, the KSHV immediate-early gene ORF50, expressed during KSHV replication, is responsible for autophagy induction.…”
mentioning
confidence: 99%
“…Among such pathogens are e.g. : poliovirus, influenza A virus, hepatitis C virus, Dengue virus (Wen et al 2010). The Kaposi's sarcoma-associated herpesvirus (KSHV), causing Kaposi's sarcoma, also belongs to viruses that adapt autophagy for their replication (Wen et al 2010).…”
Section: Autophagy In Viral Infectionsmentioning
confidence: 99%
“…Structural analyses further implicated that the two functions of vBcl-2, anti-apoptosis and anti-autophagy, engage the similar if not the same structural cassette, the hydrophobic BH3-binding groove on the surface of vBcl-2 (66,69). Yet, the affinity of vBcl-2 to Beclin1 is apparently higher than to pro-apoptotic molecules, suggesting that is recently found to induce autophagy to facilitate viral lytic replication, as blunting cellular autophagy reduces the virus's ability to reactivate from latency (78). Yet, the mechanism of RTA boosting autophagy in the lytic phase is unclear; it is also unclear whether induced autophagy is reflective of a viral-specific process or of the secondary effects of host defense.…”
Section: β-Herpesvirusmentioning
confidence: 91%